PENGARUH MEDIA MASSA TERHADAP TAHAP PERKEMBANGAN PSIKOLOGI AGAMA PADA MANUSIA - Hari Harsananda; Ida Bagus Subrahmaniam Saitya (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
The presence of mass media in the current era of globalization is nothingspecial, various kinds of media appear, grow and develop likemushrooms in the rainy season, especially with the internet that allowsconnections between individuals in this world. The media enter intopeople's lives and have an influence on one's beliefs, this is in line withthe opinion of Jhon Vivian who said that mass media is a facility thatcarries messages to the public. A person's religious behavior arisesbecause of an internal urge, which then gets an influence from theenvironment. In subsequent developments, religious behavior is muchinfluenced by factors of religious experience, personality, psychologicalelements and others. Human life experiences several phases in the levelof development of the religious soul in itself, including the children'sphase, the adolescent phase, the adult phase, and the advanced phase.Each phase has its own characteristics and uniqueness. One of theformers of religious character in these phases is the mass media. Massmedia in the present era is not only a complement but also a part of life.This media has both positive and negative influences on humans.